How to deal with vessel diameter mismatch in left main bifurcation stenting. Issue 9 (17th September 2022) - Dall'Ara, Gianni; Grotti, Simone; Compagnone, Miriam; Spartà, Daniela; Guerrieri, Giuseppe; Galvani, Marcello; Tarantino, Fabio Felice
Abstract : Left main coronary artery percutaneous coronary intervention is particularly complex when stenting across the distal bifurcation is required in the presence of a diameter mismatch between the proximal main and distal branches. A suboptimal procedural result increases the risk of thrombosis and restenosis. Considering the paucity of data published on this topic, our objective was to provide technical solutions to deal with this complex anatomy. We described four cases showing the use of devices and techniques which allowed us to overcome a diameter discrepancy between adjacent coronary segments: (1) self-expanding nitinol stent; (2) stent platform with noteworthy expansion capacity; (3) the 'extended skirt' technique; (4) the 'trouser-leg' technique. In conclusion, the use of specific strategies and devices allows a safe and effective approach to be used to perform treatment that respects the coronary anatomy, and to optimize percutaneous coronary intervention results in complex scenarios.